The Effect of Self-Discrepancy on Online Behavior: A Literature Review - Hu, Chuan; Cao, Rui; Huang, Jiao; Wei, Ying (Frontiers in Psychology, 2022)
People will experience self-discrepancy when they perceive their actual self is distanced from their ideal self and ought self. The perceived self-discrepancy has a significant impact on people’s online behavior. The goal of this paper is to provide an overview of the research on self-discrepancy in the Internet era through a literature review. A total of 37 papers were included in this review. First, this study presents the basic characteristic of the reviewed articles (such as research contexts, samples, data collection methods). Second, it summarized how the Internet affected people’s self-discrepancy. Third, this review identified how self-discrepancy was associated with different kinds of online behavior (such as impression management, knowledge contribution, gaming addiction, etc.). Finally, this study outlined several possible directions for future research.